INOVASI MANAJEMEN PEMBELAJARAN SEJARAH - Asmuni Asmuni Asmuni (UNIVERSITAS BENGKULU, 2015)
The aims of this study is to the learning management innovation in the history of the state MA 2 Lubuklinggau. The research method used in this ressearch was descriptive eva luaativequalitative approach. The data were collected by means of interviews, observation, and documentation. After that , the data collected were analyzed using qualitative descriptive technique. these results indicate that the learning management history of successful innovations by improve the quality of learning.Keyword: innovation, management